Review Strength Support Sukodono Soil Clay With Addition Stabilization Material Charcoal Wood Powder - Chrisna Maranatha S, Bona; , Agus Susanto, S.T, M.T (2017)
Based on the preliminary test results shows the soil in Sukodono, Sragen is a high plastic inorganic clay, with LL = 85.73%, PL = 24.69%, PI = 61.04% (Prasetyo, 2016). In soil chemical chemistry test conducted at UGM Chemical Analytical Chemistry Laboratory Yogyakarta, Sukodono soil contains chemical element of soil Al2O3 = 16,86%, CaO = 0,92%, Fe2O3 = 10,81%, MgO = 1,35% And SiO2 = 63.25% (Sangeoris, 2016). Based on the value of PI = 61.04% (more than 17%) then this soil is necessary for soil improvement action. Soil improvement is carried out by chemical soil stabilization using charcoal powder with a percentage of 10%, 15%, and 20% by weight of the sample. The tests include physical properties test and mechanical properties of original soil and mixed soil. The result of the physical properties of the native soil and the mixture obtained plastic limit value has increased, while the water content, density (specific gravity), liquid limit, plasticity index, shrinkage limit, and a sieve 200 percent decline. The soil mixture classification of 10% and 15% charcoal powder included the A-7-6, 20% group A-7-5. Soil mixture of charcoal wood powder 10%, 15% and 20% according to USCS system including CH group. The result of test of mechanical properties from Standard Proctor test of soil mixture of charcoal wood powder 10%, 15%, and 20% decreased value of volume weight and increase of optimum water content. The maximum weight value of the volume is 1.182 gr / cm3 and the highest optimum water content is 38% in the addition of 20% charcoal wood powder. The CBR Unsoaked value increased by 13% on the 10% increase in the percentage of charcoal wood powder. However, the decrease in the addition of 15% charcoal wood powder with a value of 11%. The smallest Unsoaked CBR value is the percentage of 20% charcoal wood powder by 10%. Keywords: clay, stabilization, charcoal wood powder, strenght support